2018
DOI: 10.3390/v10090494
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Large Genomic Deletion Is Unrelated to the Increased Virulence of the Novel Genotype Fowl Adenovirus 4 Recently Emerged in China

Abstract: Since 2015, severe hydropericardium-hepatitis syndrome (HHS), caused by a highly pathogenic fowl adenovirus 4 (FAdV-4), emerged in China. In our previous study, the FAdV-4 has been identified as a novel genotype with a unique 1966-bp nucleotide deletion (1966Del) between open reading frame 42 and 43. In this study, the natural 1966Del was frequently identified among 17 clinical isolates and other reported Chinese clinical strains. To investigate the relationship between 1966Del and the increased virulence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…To make things more intriguing, the highly pathogenic FAdV-4 loses ORF19 due to a 1966 bp deletion. However, it has been reported that the deletion of ORF19 does not contribute to the viral virulence [29,30]. We are interested in whether the remaining unique ORF19A influences the replication of the novel FAdV-4.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To make things more intriguing, the highly pathogenic FAdV-4 loses ORF19 due to a 1966 bp deletion. However, it has been reported that the deletion of ORF19 does not contribute to the viral virulence [29,30]. We are interested in whether the remaining unique ORF19A influences the replication of the novel FAdV-4.…”
Section: Discussionmentioning
confidence: 98%
“…This platform was further modified and improved by Eva Nagy and her colleagues through introducing phage recombinase [10]. Recently, CRISPR/Cas9 was employed as a tool to introduce double-stranded breaks at targeting site in FAdV genome to increase the percentage of positive recombinants in eukaryotic cells [29]. The homologous recombination in bacteria with phage recombinase and counter-selection technique were combined and used for modifying the FAdV-4 genome [30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus PX-induced apoptosis contributed at least in part to FAdV4-induced apoptosis, which facilitates viral replication. Up to now, some researchers have established a reverse genetic system to generate recombinant FAdV4 [34] or used the CRISPR/cas9 system to delete or insert some nucleotide fragments directly [4]. Therefore, more efforts will be required to investigate the role of PX in the pathogenesis of FAdV4 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the FAdV4 strains that recently emerged in China had the same deletion of 1966 bp in the genome compared with the non-virulent FAdV4 viruses (ON1 strain) [2]. However, the experimental evidence shows that the natural deficiency of 1966 bp in the viral genome was not essential for the increased virulence of the recently isolated FAdV4 in China [4]. Currently, the virulence-associated factors of FAdV4 responsible for clinical HHS are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to our findings, all of the viruses previously isolated from China had a similar deletion of nucleotides ( Liu et al., 2016 ). It was speculated that this deletion might have a role in the pathogenicity of these isolates, but recent studies using the clustered regularly interspaced short palindromic repeat ( CRISPR ) and CRISPR associated protein 9 ( CRISPR – Cas9 ) system found that this deletion was dispensable for the high pathogenicity of such isolates ( Pan et al., 2018 ). The 6-bp deletion in all 9 isolates at position 28,784, when compared with the ON1 genome, was also present in HNJZ, indicating this deletion was specific to Chinese isolates.…”
Section: Discussionmentioning
confidence: 99%